THE EFFECT OF INTERNAL COMMUNICATION AND EMPLOYEE WELL-BEING ON EMPLOYEE PERFORMANCE, MEDIATED THRU EMPLYEE ENGAGEMENT (STUDY AT PT WUZA) - Adi Sumarno; M. Ali Iqbal (Dinasti Publisher, 2022)
In general, this study is to analyses employee performance impacted by communication and well-being. This study aims to analyses the effect of internal communication and employee well-being on employee performance through employee engagement mediation. The number of samples was determined using the Slovin formula and the results were found to be 97 samples. This study uses a quantitative analysis approach with data collection methods through questionnaires given to 220 respondents. The data analysis method in this study is the Structural Equation Model (SEM) with the Smart PLS analysis tool. The results show that internal communication has no significant effect on employee engagement, internal communication has a significant effect on employee performance, employee well-being has a significant effect on employee engagement, employee well-being has a significant effect on employee performance, employee engagement has no significant effect on employee performance, employee engagement does not mediate internal communication on employee performance and employee engagement does not mediate employee well-being on employee performance.